칼슘 실리케이트 계열 실러가 흰쥐의 하악골 조직에 미치는 영향 - 태지선(Jee-Seon Tae); 유기연(Ki-Yeon Yoo); 김진우(Jin-Woo Kim); 조경모(Kyung-Mo Cho); 이윤(Yoon Lee); 박세희(Se-Hee Park) (Journal of dental rehabilitation and applied science, 2024)
Purpose: To histologically evaluate the effects of three calcium silicate-based sealers on rat mandible tissue. Materials and Methods: Rats were randomly divided as follows: A group that sacrificed immediately after cavity preparation, a group that sacrificed two weeks after cavity preparation, a group that sacrificed two weeks after CeraSeal (CS), AH Plus Bioceramic (AHB), or One-Fil (OF) sealer injection, respectively. After tissue processing for all groups, the bone tissue area (%) and the number of osteoclasts in and around the cavity were measured under a microscope. The results of each group were compared and statistical analysis was performed using one-way ANOVA and Tukey's test. Results: The formation of bone tissue and the presence of osteoclasts in the cavity were observed in the group that sacrificed two weeks after cavity preparation and the group sacrificed two weeks after AHB sealer injection, and these groups showed significantly higher average bone tissue area (%) than the other groups. In the other groups, no inflammation or foreign body reaction occurred in the cavity, and no osteoclasts were observed. Conclusion: All calcium silicate-based sealers used in this study showed a favorable bone tissue response when injected into the rat mandible. In particular, higher bone formation in the cavity was observed in AHB. 목적: 세 가지 칼슘 실리케이트 계열 실러가 흰쥐 하악골 조직에 미치는 영향을 조직학적으로 평가하고자 하였다. 연구 재료 및 방법: 흰쥐의 하악골에 와동을 형성하고 즉시 또는 2주 후 희생한 군, 와동에 CeraSeal (CS), AH Plus Bioceramic (AHB), One-Fil (OF) 실러를 각각 주입하여 2주 후 희생한 군으로 무작위 배정하였다. 모든 군을 조직 처리하고 현미경 하에서 와동 내외 평균 골 면적 분율(%)을 계산하고 파골세포를 계수하였고, 각 군의 결과를 비교하고 일원분산 분석 및 Tukey's test로 통계 분석하였다. 결과: 와동 형성 2주 후 희생한 대조군과 AHB 실러 주입 2주 후 희생한 군에서 와동 내 골조직 형성과 파골세포의 존재를 확인할 수 있었고, 다른 군들에 비해 유의하게 높은 와동 내 골 면적 분율(%)을 보여주었다. 다른 군들에서는 와동 내 어떠한 염증이나 이물 반응이 나타나지 않고 파골세포 또한 관찰되지 않았다. 결론: 실험에 사용된 칼슘 실리케이트 계열 실러는 흰쥐 하악골에 주입하였을 때 양호한 골조직 반응을 보였고, 특히 AHB에서 더 높은 와동 내 골조직 형성이 관찰되었다.